2015
DOI: 10.1136/bcr-2015-211521
|View full text |Cite
|
Sign up to set email alerts
|

Multiple embolic cerebral infarcts as the first manifestation of metastatic ovarian cancer

Abstract: SUMMARYA 36-year-old woman presented to the emergency department with a 3-day history of an occipital headache associated with transient visual impairment and short-term memory loss. MRI of the brain showed innumerable focal embolic infarcts of differing ages, for which a cause could not be determined. The patient was discharged and readmitted 7 weeks later with acute aphasia and a right-sided hemiplegia. CT of the abdomen revealed a right-sided ovarian mass and prominent retroperitoneal nodes, which cytology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…21 Cerebral ischemia might occur due to embolus metastatic glioma cells, as reported recently. 22 Another unusual case of acute ischemic infarction of the middle cerebral artery was caused by a proliferating glioma mass. 23 In certain cases, it is notably difficult to distinguish the early symptoms of stroke and glioma, which might lead to improper therapy.…”
Section: Interplay Between Cerebral Ischemia and Glioma: What Do Clinmentioning
confidence: 99%
“…21 Cerebral ischemia might occur due to embolus metastatic glioma cells, as reported recently. 22 Another unusual case of acute ischemic infarction of the middle cerebral artery was caused by a proliferating glioma mass. 23 In certain cases, it is notably difficult to distinguish the early symptoms of stroke and glioma, which might lead to improper therapy.…”
Section: Interplay Between Cerebral Ischemia and Glioma: What Do Clinmentioning
confidence: 99%
“…Seven previous case series (16 patients) with DWI sequence were also analyzed in our study 3,7‐13 . The mean age of the total patients (21 patients) was 66 years (mean ± SD, 66 ± 11.74 years).…”
Section: Resultsmentioning
confidence: 99%
“…A previous population‐based study reported an increased risk of ischemic stroke in OC patients 19 . In addition, some case reports reported stroke and multiple embolic cerebral infarcts as the first manifestations of ovarian cancer 20, 21 …”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, some case reports reported stroke and multiple embolic cerebral infarcts as the first manifestations of ovarian cancer. 20,21 Regarding death due to other (non-ovary) cancers, risk of death decreases with time after OC diagnosis. These findings agree with a previous Canadian study on patients with epithelial OC, 22 where other cancers were the second highest death cause in long-term OC survivors, after OC.…”
Section: Discussionmentioning
confidence: 99%